Atrial Septal Defect secundum with inferior floppy rim in the elderly: surgical closure or transcatheter closure? A case report - Irawati Hajar Kikuko; Achmad Lefi; Steve Freyssinet Karundeng; Agus Subagjo; A’ Rofah Nurlina Puspitasari; Alqi Yutha (Journal of the Pakistan Medical Association)
Atrial Septal Defect closure in childhood and early adulthood has a good prognosis, but in older individuals the risk-benefit ratio is not as straightforward. We report a 57-year-old man who was easily fatigued when exercising. The cardiac examination revealed a wide and fixed splitting of S2, a pulmonary ejection systolic murmur grade III/VI, and increased jugular venous pressure. The transesophageal echocardiography showed Atrial Septal Defect secundum with a diameter of 20 mm, L-to-R shunt, and 5 mm, a thin and floppy inferior rim. The patient underwent surgical Atrial Septal Defect closure. The deficient posteroinferior rim occurs only in 3.3% of patients with secundum Atrial Septal Defect. This condition will enhance the likelihood of occluder dislodgement in the transcatheter closure approach. We learn from this case that surgical Atrial Septal Defect closure may be an option for elderly patients if there is an inadequate, thin, and floppy inferior rim or no comorbidities. Keywords: Systolic Murmurs, Thoracic Surgical, Vital Signs, Heart Murmurs, Prognosis